Modified pubovaginal sling technique in the surgical management of female stress urinary incontinence - Frade,Armando Brites (2015)
Objective: To assess the application of aponeurotic sling by a modified technique with direct visualization of needles in patients with stress urinary incontinence. Methods: we applied the Kings Health Questionnaire (KHQ) for quality of life, gynecological examination, urinalysis I and urine culture approximately seven days prior to the urodynamic study (UDS) and the one-hour PAD test in patients undergoing making aponeurotic sling with its passing through the retropubic route with direct visualization of the needle, PAD test and King's Helth Questionnaire before and after surgery. Results: The mean age was 50.6 years, BMI of 28 and Leak Pressure (LP) 58,5cm H2O; 89% were Caucasian. Forty-six of them were monitored for three and six months, 43 for 12 months. The objective cure rate at 12 months postoperatively was approximately 93.5%. In evaluating quality of life, we observed a significant improvement in 12 months postoperatively compared with the preoperative period. There was no no urethral/bladder injury. As adverse results, we had one persistent urinary retention (2.3%), who was submitted to urethrolysis, currently without incontinence. Conclusion: The proposed procedure is safe as for the risk of bladder or urethral injuries, promoting significant improvement in quality of life and objective cure.